Migration, transnationalism, and the spaces of class identity - Kelly, Philip F. (Philippine studies : historical and ethnographic viewpoints, 2012)
"To make sense of the diversity in contemporary understandings of class, this article proposes a four-part typology, with class understood as "position," "process," "performance," and "politics." Each highlights a distinct dimension of class, but all are closely related to each other. The article uses research on Filipino migration to Canada to show that the downward class mobility experienced by many immigrants can only be adequately understood when all of these dimensions of class are integrated into an analysis and when the process of immigration is understood in a transnational frame. The article uses qualitative data collected from Filipino immigrants in Canada to show how subjective understandings of class provide meaningful ways of reconciling a process of downward mobility."